Systematic Literature Review Methodology for Drone Recharging Processes in Agriculture and Disaster Management - Leonardo Grando; Juan Fernando Galindo Jaramillo; José Roberto Emiliano Leite; Edson Luiz Ursini (Drones)
Unmanned Aerial Vehicles (UAVs), or drones, are becoming increasingly vital in agriculture and disaster management due to their autonomous monitoring, data collection, and service delivery capability. However, energy constraints often limit their potential, highlighting the need for efficient recharging and energy management solutions. This systematic literature review (SLR) examines the current simulations of drone recharging technologies within precision agriculture and disaster relief. It highlights recent advancements, including various algorithms for path and mission planning, while identifying ongoing challenges, particularly the scarcity of studies on the recharging coordination that affects UAV operations in these fields. The review encompasses 36 high-quality studies from 2038 papers initially found in the literature. Despite significant progress in recharging technologies, achieving sustainable and continuous UAV operation remains challenging, especially in high-demand energy environments such as disaster zones and agricultural areas. We identify three research gaps—knowledge, methodological, and practical. There is a lack of drone recharging studies, as drones are energy-demanding devices. The studies show that the coordination process relies on communication, which can use more battery, and we also find a lack of real-world applications in the studies. Another finding is that the context of disaster is studied more than agricultural usage.